Unveiling the Bioleaching Versatility of Acidithiobacillus ferrooxidans - Luca Tonietti; Mattia Esposito; Martina Cascone; Bernardo Barosa; Stefano Fiscale; Maria Teresa Muscari Tomajoli; Tomasa Sbaffi; Rosa Santomartino; Giovanni Covone; Angelina Cordone; Alessandra Rotundi; Donato Giovannelli (Microorganisms)
Acidithiobacillus ferrooxidans is a Gram-negative bacterium that thrives in extreme acidic conditions. It has emerged as a key player in biomining and bioleaching technologies thanks to its unique ability to mobilize a wide spectrum of elements, such as Li, P, V, Cr, Fe, Ni, Cu, Zn, Ga, As, Mo, W, Pb, U, and its role in ferrous iron oxidation and reduction. A. ferrooxidans catalyzes the extraction of elements by generating iron (III) ions in oxic conditions, which are able to react with metal sulfides. This review explores the bacterium’s versatility in metal and elemental mobilization, with a focus on the mechanisms involved, encompassing its role in the recovery of industrially relevant elements from ores. The application of biomining technologies leveraging the bacterium’s natural capabilities not only enhances element recovery efficiency, but also reduces reliance on conventional energy-intensive methods, aligning with the global trend towards more sustainable mining practices. However, its use in biometallurgical applications poses environmental issues through its effect on the pH levels in bioleaching systems, which produce acid mine drainage in rivers and lakes adjacent to mines. This dual effect underscores its potential to shape the future of responsible mining practices, including potentially in space, and highlights the importance of monitoring acidic releases in the environment.